Let us define the Bernoulli numbers $B_{i}$, for all natural numbers $i \geq 0$, by

(1) $\frac {X}{e^{X} - 1} = \sum_{i=0}^{\infty} \frac{B_{i}}{i!}X^{i}$,

where $X$ is a variable. (The first member is a well defined formal power series in $X$, let us say over $\mathbb{C}$, thus this definition makes sense.)

A well known theorem of von Staudt has the following special case :

(2) For every prime number $p$, $p B_{p-1}$ is a $p$-integral rational number congruent with -1 modulo $p$.

I got the following strengthening as a by-product :

(3) For every prime number $p$, $p B_{p-1}$ is a $p$-integral rational number congruent with $p + (p-1) !$ modulo $p^{2}$.

(In view of Wilson's theorem, (3) implies (2).)

The proof that I can extract from my work is very heavy, so I wonder if someone could know or could find a more straightforward proof. Here is the mine. It is true for $p = 2$, thus we can assume that $p$ is odd.

The formal power series $Log (1-X)$ is divisible by $X$ (in the ring $\mathbb{C}[[X]]$ of formal power series in $X$), thus we can replace $X$ by $Log (1-X)$ in (1). We find

(4) $\frac{Log (1-X)}{-X} = \sum_{i=0}^{\infty} \frac{B_{i}}{i!}(Log (1-X))^{i}$.

Let $p$ be a fixed odd prime number. For every rational integer $i$, let us define $f_{i}(X)$ (the $i$-th Mirimanoff polynomial with regard to $p$) as

$f_{i}(X) = \sum_{r=1}^{p-1} r^{i-1} X^{r}$.


(5) $Log (1-X) \equiv - f_{0}(X) - \frac{X^{p}}{p} (mod\ X^{p+1})$

in the ring $\mathbb{C}[[X]]$. Dividing both members and the modulus of this congruence by $X$ gives

(6) $\frac{Log (1-X)}{X} \equiv - \frac{f_{0}(X)}{X} - \frac{X^{p-1}}{p} (mod\ X^{p}).$

Thus (4) gives

(7) $\frac{f_{0}(X)}{X} + \frac{X^{p-1}}{p} \equiv \sum_{i=0}^{\infty} \frac{B_{i}}{i!}(Log (1-X))^{i} (mod\ X^{p})$

in the ring $\mathbb{C}[[X]]$.

Relation (5) implies the weaker relation

$Log (1-X) \equiv - f_{0}(X) (mod\ X^{p})$

thus (7) gives

(8) $\frac{f_{0}(X)}{X} + \frac{X^{p-1}}{p} \equiv \sum_{i=0}^{\infty} \frac{B_{i}}{i!} (-1)^{i} f_{0}(X)^{i} (mod\ X^{p})$

in the ring $\mathbb{C}[[X]]$. Since this is a congruence modulo $X^{p}$ and $f_{0}(X)^{i}$ is divisible by $X^{i}$, we can neglect the values $\geq p$ of $i$, so we obtain a congruence in the polynomial ring $\mathbb{Q}[X]$ :

$\frac{f_{0}(X)}{X} + \frac{X^{p-1}}{p} \equiv \sum_{i=0}^{p-1} \frac{B_{i}}{i!} (-1)^{i} f_{0}(X)^{i} (mod\ X^{p})$

in the polynomial ring $\mathbb{Q}[X]$. Isolating the values 0 and $p-1$ of $i$, we put this under the form

(9) $\frac{f_{0}(X)}{X} + \frac{X^{p-1}}{p} \equiv 1 + \sum_{i=1}^{p-2} \frac{B_{i}}{i!} (-1)^{i} f_{0}(X)^{i} + \frac{B_{p-1}}{(p-1)!} f_{0}(X)^{p-1} (mod\ X^{p})$

in the polynomial ring $\mathbb{Q}[X]$.

Now we need the following fact :

(10) for $1 \leq j \leq p-2$, the coefficient of $X^{p-1}$ in $f_{0}(X)^{j}$ is congruent to $- j !$ modulo $p$.

This can be deduced from the following result of Mirimanoff :

for $1 \leq j \leq p-2$,

$f_{0}(X)^{j} \equiv (-1)^{j-1} j! f_{p-j}(1-X) (mod\ p \mathbb{Z}_{(p)}[X] + X^{p} \mathbb{Z}_{(p)}[X])$,

where $\mathbb{Z}_{(p)}$ denotes the ring of $p$-integral rational numbers.

(See D. Mirimanoff, "L'équation indéterminée $x^{l} + y^{l} + z^{l} = 0$ et le critérium de Kummer", Journal für die reine und angewandte Mathematik, vol. 128, 1905, p. 45-68, spec. p. 60-61. It is on https://gdz.sub.uni-goettingen.de/ )

In view of (10) and the fact that $B_{1}, B_{2}, ..., B_{p-2}$ are $p$-integral, considering the terms in $X^{p-1}$ in (9) gives

$\frac{1}{p} \equiv - \sum_{i=1}^{p-2} (-1)^{i}B_{i} + \frac{B_{p-1}}{(p-1)!} (mod\ p)$

(defining that two non $p$-integral numbers are congruent modulo $p$ if their difference is $p$-integral and divisible by $p$ in $\mathbb{Z}_{(p)}$).

This result can also be written

(11) $\frac{1}{p} \equiv 1 - \sum_{i=0}^{p-2} (-1)^{i}B_{i} + \frac{B_{p-1}}{(p-1)!} (mod\ p)$.

But $\sum_{i=0}^{p-2} (-1)^{i}B_{i} \equiv 0 (mod\ p)$. (Note that $B_{1} = -1/2$ and $B_{i} = 0$ if $i$ is odd and > 1, and use Congruence between Bernoulli numbers )

Thus (11) gives

$\frac{B_{p-1}}{(p-1)!} \equiv \frac{1}{p} - 1 (mod\ p).$

Multiplying by $p (p-1)!$, we get a congruence modulo $p^{2}$ :

$p B_{p-1} \equiv (p-1)! - p (p-1)! (mod\ p^{2})$.

In view of Wilson's theorem, $ (p-1)! \equiv - 1 (mod\ p)$, thus $p (p-1)! \equiv -p (mod\ p^{2})$ and (3) is proven.

Let me indicate without proof that the following can be deduced from (3) :

If $p$ is a prime number $\geq 5$, if $j$ is a natural number $\geq 1$, then

$p B_{j(p-1)} \equiv j (1 + (p-1)!) + p - 1 (mod\ p^{2})$.

In view of Wilson's theorem, it is a strengthening of von Staudt's theorem (but only valid for $p \geq 5$).

As I said, I find that my proof of (3) is very heavy and I would be interested by a simpler proof, and also by a reference to the literature. Thanks in advance.


By Faulhaber's formula $$\sum_{k=1}^n k^{p-1}=\frac{n^p}{p} +\frac{n^{p-1}}{2}+\cdots+B_{n-1}n$$ where the omitted terms have coefficients that are $p$-integers (von Staudt). This means that $$B_{p-1}p\equiv\sum_{k=1}^p k^{p-1}\equiv\sum_{k=1}^{p-1} k^{p-1}\pmod{p^2}$$ So all we need is $$p+(p-1)!\equiv\sum_{k=1}^{p-1}k^{p-1}\pmod{p^2}.\tag{*}$$ This congruence was proved by Lerch. See this paper by Sondow and MacMillan.

Here's a summary of their proof. We can write $k^{p-1}=1+pa_k$ for $p\nmid k$. Then $$\sum_{k=1}^{p-1}k^{p-1}=-1+p+p(a_1+a_2+\cdots+a_{p-1})$$ and $$(p-1)!^{p-1}=(1+pa_1)(1+pa_2)\cdots (1+pa_{p-1}) \equiv1+p(a_1+a_2+\cdots+a_{p-1})\pmod {p^2}.$$ Write $(p-1)!=pb-1$ with $b\in\Bbb Z$. Then $$(p-1)!^{p-1}=(1-pb)^{p-1} \equiv1+bp\equiv(p-1)!+2\pmod{p^2}.$$ We conclude that $$\sum_{k=1}^{p-1}k^{p-1}\equiv-2+p+(p-1)!^{p-1}\equiv p+(p-1)! \pmod{p^2}.$$

  • $\begingroup$ It seems that thanks are deprecated on Stackexchange, but I thank you very much. $\endgroup$ – Panurge Apr 28 '18 at 6:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.